Rancang Bangun Penyiram Tanaman Cabai Otomatis Berbasis Arduino Dengan Sumber Daya Panel Surya - Faqih Alvrido; Sunardi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
In this study, it aims to make it easier for farmers to do watering. here researchers use chili plants, because chili is one of the human food needs. The sensor components used in this plant watering prototype tool are soil moisture sensors, ESP 8266 modules, DHT 11 sensors, RTC (Real Time Clock) and buzzers. And for the microcontroller used by researchers is the Arduino Mega 2560. Researchers use Arduino Mega 2560 because it has more memory than Arduino Uno. This tool uses energy from solar power to power it. Researchers use solar panels to generate electricity from the heat of the sun. Solar energy absorbed by solar panels will be converted into electrical energy by the Solar Charge Controller (SCC), and the electrical energy will be stored in a special battery, namely a Lithium ion battery. From the basic testing of chili plant sprinklers that have been carried out as a whole, the pump waters the chili plants based on soil moisture with humidity (<50%) and a predetermined time. When the soil moisture (>70%) the pump will stop watering, and the specified watering time is 3x a day. To set the time of the watering schedule, researchers use the ESP 8266 module so that it can be set through the BLYNK application on a cellphone. Researchers also apply manual schedule settings on the panel box by pressing the switch button. With the creation of this Arduino-based Automatic Plant Sprinkler prototype with Solar Panel Resources to make it easier for chili farmers to produce a satisfying harvest, and save time when watering.